Um modelo fuzzy-dea-game para estratégias de produção sob incerteza - Silva, Aneirson Francisco da [UNESP]; Miranda, Rafael de Carvalho; Silva Marins, Fernando Augusto [UNESP] (Fundacao Getulio Vargas, 2015)
This study develops a new Fuzzy-DEA-Game (FOG) model to support the establishment of production strategies. This model combines Data Envelopment Analysis (DEA) with concepts of Fuzzy Set Theory and Nash Bargaining Game. The model permits an evaluation of the productive and economic efficiency of products, which may result in a portfolio of more profitable products with greater consumer market interest. The model was applied at an energy company. The results obtained applying the FOG model adhered to the reality of the studied company and provided goals for reducing resource levels (inputs) needed for manufacturing products and for increasing result levels (output) stemming from their commercialization. As an important additional outcome, the FDG model permitted the identification of portfolio products that are more sensitive to the occurrence of uncertainty.
A Fuzzy-DEA-Game model for production strategies in uncertainty
Keywords: Production strategies; Uncertainty; Data envelopment analysis; Bargaining games; Fuzzy set theory